ANALISA TINGKAT KEPUASAN KELUARGA PASIEN DI PELAYANAN PENDAFTARAN PASIEN INSTALASI GAWAT DARURAT DI RUMAH SAKIT MENTENG MITRA AFIA - Meliana; Meta Arnelita (MEDICORDHIF Jurnal Rekam Medis, 2022)
This study was conducted to obtain an overview of the patient's family satisfaction with services at the emergency room (ER) patient registration section at Menteng Mitra Afia Hospital. The place of this research was carried out at the emergency room (ER) patient registration site at Menteng Mitra Afia Hospital in June 2021 using a qualitative descriptive analysis method with data collection by direct observation and interviews with registration officers. The sample from this study collected 178 patient families obtained from the total patient family population in January, February and March 2021. Registration is the beginning of a hospital service. This is where the importance of the role of a registration officer must be able to give a good impression so that the patient's family can feel satisfaction from hospital services. Dimensions of satisfaction consist of 5 namely Responsiveness (responsiveness), Reliability (reliability), Assurance (guarantee), Empathy (empathy), Tangibles (display/physical evidence). The results of the study were based on 5 dimensions of service quality for emergency room (ER) patient registration, namely Responsiveness (responsiveness) 77.00% satisfied category, 16.40% neutral category, and 6.85% dissatisfied category. The reliability of the satisfied category is 76.63%, the neutral category is 15.17%, and the dissatisfied category is 8.11%. Guarantee (Guarantee) in the category of 76.40% satisfied, 17.98% neutral category, and 5.28% dissatisfied category. Empathy (Empathy) is 75.06% satisfied category, 19.66% neutral category, and 5.28% dissatisfied category. Tangibles (display/physical evidence) in the satisfied category is 66.52%, the neutral category is 19.78%, and the dissatisfied category is 13.71%.